Magnetic resonance perfusion diffusion mismatch and thrombolysis in acute ischaemic stroke: a systematic review of the evidence to date. Issue 5 (20th October 2006) - Kane, I; Sandercock, P; Wardlaw, J
Abstract : Background: The mismatch between perfusion and diffusion lesions on magnetic resonance perfusion-weighted imaging (PWI)/diffusion-weighted imaging (DWI) may help identify patients for thrombolysis. Evidence underlying this hypothesis was assessed. Methods: All papers describing magnetic resonance PWI/DWI findings in patients with acute ischaemic stroke, and their functional and/or radiological outcome at 1 month, with or without thrombolysis were systematically reviewed. Results: 11 papers fulfilled the inclusion criteria. Among these, there were 5 different mismatch definitions and at least 7 different PWI methods. Only 3 papers including 61 patients with and 18 without mismatch provided data on mismatch, outcome and influence of thrombolysis. Mismatch ( v no mismatch) without thrombolysis was associated with a non-significant twofold increase in the odds of infarct expansion (odds ratio (OR) 2.2, 95% confidence interval (CI) 0.34 to 14.1), which did not change with thrombolysis (OR 2.0, 95% CI 0.37 to 10.9). Half of the patients without mismatch also had infarct growth (with or without thrombolysis). No data were available on functional outcome. Conclusions: Standardised definitions of mismatch and perfusion are needed. Infarct growth may occur even in the absence of mismatch. Currently, data available on mismatch are too limited to guide thrombolysis in routine practice. More data are needed from studies including patients with and without mismatch, and randomised treatment allocation, to determine the role of mismatch.